Does laser diode irradiation improve the degree of conversion of simplified dentin bonding systems? - Leticia Ferreira de Freitas BRIANEZZI; Rafael Massunari MAENOSONO; Odair BIM JÚNIOR; Giovanna Speranza ZABEU; Regina Guenka PALMA-DIBB; Sérgio Kiyoshi ISHIKIRIAMA
Abstract Simplified dentin-bonding systems are clinically employed for most adhesive procedures, and they are prone to hydrolytic degradation. Objective This study aimed to investigate the effect of laser diode irradiation on the degree of conversion (DC), water sorption (WS), and water solubility (WSB) of these bonding systems in an attempt to improve their physico-mechanical resistance. Material and Methods Two bonding agents were tested: a two-step total-etch system [Adper™ Single Bond 2, 3M ESPE (SB)] and a universal system [Adper™ Single Bond Universal, 3M ESPE (SU)]. Square-shaped specimens were prepared and assigned into 4 groups (n=5): SB and SU (control groups - no laser irradiation) and SB-L and SU-L [SB and SU laser (L) - irradiated groups]. DC was assessed using Fourier transform infrared spectroscopy with attenuated total reflectance. Additional uncured resin samples (≈3.0 µL, n=5) of each adhesive were also scanned for final DC calculation. For WS/WSB tests, similar specimens (n=10) were prepared and measured by monitoring the mass changes after dehydration/water storage cycles. For both tests, adhesive fluids were dropped into standardized Teflon molds (6.0×6.0×1.0 mm), irradiated with a 970-nm laser diode, and then polymerized with an LED-curing unit (1 W/cm2). Results Laser irradiation immediately before photopolymerization increased the DC (%) of the tested adhesives: SB-L>SB>SU-L>SU. For WS/WSB (μg/mm3), only the dentin bonding system (DBS) was a significant factor (p<0.05): SB>SU. Conclusion Irradiation with a laser diode improved the degree of conversion of all tested simplified dentin bonding systems, with no impact on water sorption and solubility.